Case Report: Helminths Infestation with Bronchopneumonia and Tick Infestation in Mixed Dog - Nesa, Ni Luh Mentari Saavitri; Sisyawati, Putu Ayu; Erawan, I Gusti Made Krisna (Journal of Veterinary and Animal Sciences; Vol 6 No 1 (2023)DO - 10.24843/JVAS.2023.v06.i01.p05, 2023)
Abstract. A mixed-breed dog named Vino, male, golden brown, two years old, weighing 10 kg was brought to the Veterinary Internal Medicine Laboratory, Faculty of Veterinary Medicine, Udayana University with a non-productive cough four months before the examination. Two weeks after the onset of the cough, the dog showed signs of itching. There were blood spots in the feces and the consistency is very soft but still has shape. Respiratory examination revealed that the case dog had a non-productive cough. Auscultation of the lungs revealed deep breathing and slight crackles. Skin examination revealed Rhipicephalus sp. Infestation with ulcerative lesions, erythema, papules, hyperpigmentation, lichenification, and alopecia. On radiography, there was a bronchial pattern and radiopaque spots in the lungs. The results of the complete blood count showed leukocytosis, mild neutrophilia, eosinophilia, and mild hypochromia. Stool examination revealed the presence of Ancylostoma spp. and Strongyloides spp. eggs. Examination of the impression smear and tape acetate preparation test with cytologic staining revealed some neutrophils. The case dog was diagnosed with Ancylostoma spp. and Strongyloides spp. infestation accompanied by bronchopneumonia and tick infestation. Treatment was administered with Caniverm ® , Advocate ® , and methylprednisolone. After 14 days of treatment, the dog's condition improved, as evidenced by no worm eggs found in the feces and the case dog was no coughing or scratching by the case dog, and no ticks found on the case dog's body.